2008
DOI: 10.1007/s11431-008-0109-6
|View full text |Cite
|
Sign up to set email alerts
|

In situ preparation of nanoparticles/polymer composites

Abstract: Nanoparticle (NP) is the matter between molecule and bulk material. It has attracted much attention in catalysis, optoelectronics and biology due to its unique physical and chemical properties. Incorporation of these NPs into the polymer matrix is one of the best methods to display their special functions, which not only stabilize the NPs but also realize the functional assembly of NPs and polymers. However, realization of this idea depends largely on the compatibility of NPs and polymers as well as the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 97 publications
0
9
0
1
Order By: Relevance
“…Current applications have used unique properties of nanoparticles to be delivered as fillers of composites or as coating materials. It is the property of this polymer-nanoparticle composite that has enhanced the flexibility, stability, and the conformational ability for the formation of complicated structures, while retaining the nanoparticle traits [158][159][160]. While the polymer network serves as a template medium, it also acts as the stabilizing agent for the nanoparticles on a long-term basis and proves to be a landmark in protecting their usability and function.…”
Section: Composite Fibersmentioning
confidence: 99%
“…Current applications have used unique properties of nanoparticles to be delivered as fillers of composites or as coating materials. It is the property of this polymer-nanoparticle composite that has enhanced the flexibility, stability, and the conformational ability for the formation of complicated structures, while retaining the nanoparticle traits [158][159][160]. While the polymer network serves as a template medium, it also acts as the stabilizing agent for the nanoparticles on a long-term basis and proves to be a landmark in protecting their usability and function.…”
Section: Composite Fibersmentioning
confidence: 99%
“…One of them is to obtain uniform dispersion of the nanoparticles in the polymer matrixes, preventing them from leaching or adhering to each other. One approach could be to connect the particles to the polymers via covalent bonds or functionalize them in order to improve compatibility with the attractive interactions of polymer chains through van der Waals forces or hydrogen-bonds via blending (Akagi et al, 2010;Jeon and Baek, 2010), in situ polymerization (Li and Sun, 2010;Sun and Yang, 2008), sol-gel (Schmidt et al, 2000) and layer-by-layer (Kotov, 2003) methods.…”
Section: Polymeric Membranes: From Glassy To Rubbery Membranesmentioning
confidence: 99%
“…Halik et al [1] demonstrated that large operating voltages were not an intrinsic feature of organic transistors, and the operating voltages and power dissipations of organic devices could be dramatically reduced by using extreme thin self-assembly film of silane-based molecular as dielectric. Apart from reducing the thickness of gate dielectric, many other methods [3][4][5][6][7][8][9][10][11][12][13][14] have been proposed to lower down the operating voltages and threshold voltages (V T ). The most attractive one among them is considered to be applying high-k material [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from reducing the thickness of gate dielectric, many other methods [3][4][5][6][7][8][9][10][11][12][13][14] have been proposed to lower down the operating voltages and threshold voltages (V T ). The most attractive one among them is considered to be applying high-k material [2][3][4][5][6][7][8][9][10][11][12][13][14]. Until now, the reported high-k materials used in OFETs include HfO 2 [3], Al 2 O 3 [4], Barium Zirconate Titanate (BZT) [5], BZN (Bi 1.5 Zn 1.0 Nb 1.5 O 7 ) [6], SBT (SrBi 2 Ta 2 O 9 ) [7], Ta 2 O 5 [8], TiO 2 [9], and ZrO 2 [10,11].…”
Section: Introductionmentioning
confidence: 99%